2010
DOI: 10.1139/g10-048
|View full text |Cite
|
Sign up to set email alerts
|

Sequence characterization and phylogenetic analysis of the 5S ribosomal DNA in species of the family Batrachoididae

Abstract: 5S ribosomal DNA (rDNA) sequences were analyzed in four species belonging to different genera of the fish family Batrachoididae. Several 5S rDNA variants differing in their non-transcribed spacers (NTSs) were found and were grouped into two main types. Two species showed both types of 5S rDNA, whereas the other two species showed only one type. One type of NTS of Amphichthys cryptocentrus showed a high polymorphism due to several deletions and insertions, and phylogenetic analysis showed a between-species clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…The occurrence of microsatellites in the NTSs has been reported in several marine organisms (Ota et al, 2003;Alves-Costa et al, 2006), and it seems to be a common feature in the Chondrichthyes group (Rocco et al, 2005;Pasolini et al, 2006;Pinhal et al, 2009). Some authors have suggested that the presence of microsatellite sequences favours the maintenance of tandem arrays of multigene families (Liao and Weiner, 1995;Úbeda-Manzanaro et al, 2010b). Microsatellites can stabilize DNA structures, acting as "hot spots" for recombination, and therefore might function as an initiation site for the main mechanisms of concerted evolution, such as gene conversion or unequal cross-over (Liao and Weiner, 1995;Chistiakov et al, 2006).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The occurrence of microsatellites in the NTSs has been reported in several marine organisms (Ota et al, 2003;Alves-Costa et al, 2006), and it seems to be a common feature in the Chondrichthyes group (Rocco et al, 2005;Pasolini et al, 2006;Pinhal et al, 2009). Some authors have suggested that the presence of microsatellite sequences favours the maintenance of tandem arrays of multigene families (Liao and Weiner, 1995;Úbeda-Manzanaro et al, 2010b). Microsatellites can stabilize DNA structures, acting as "hot spots" for recombination, and therefore might function as an initiation site for the main mechanisms of concerted evolution, such as gene conversion or unequal cross-over (Liao and Weiner, 1995;Chistiakov et al, 2006).…”
Section: Resultsmentioning
confidence: 96%
“…These families fundamentally evolve in a concerted fashion, in which the sequences of the units are homogenised by various mechanisms as gene conversion or unequal crossing-over. However, some authors have reported an alternative evolution model (birth-anddeath model) of these multigene families in other species (Úbeda-Manzanaro et al, 2010b;Vierna et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, given the high degree of homogeneity in the 5S rRNA genes usually observed within species, several authors have used them as species-specific markers [Manchado et al, 2006a]. In other studies, however, intensive dynamism has been observed in this gene, leading to phenomena such as pseudogenes [Frederiksen et al, 1997;Martins et al, 2002;Freire et al, 2010], different types of 5S rDNA [Vierna et al, 2009;Freire et al, 2010;Úbeda-Manzanaro et al, 2010a] and linkage to other multigene families [Drouin and Moniz de Sá, 1995;Manchado et al, 2006b;Freire et al, 2010]. Recent studies have shown the presence of elements such as tRNA-derived short interspersed nuclear elements (SINEs), long terminal repeats (LTRs) and microsatellites, among others, in the NTSs of fishes ( fig.…”
Section: Evolution Of the 5s Rdna: Concerted Evolution Versus Birth-amentioning
confidence: 99%
“…Therefore, an increasing number of authors have rejected the exclusivity of concerted evolution as the model which explains the 5S rDNA evolution [Rooney and Ward, 2005;Fujiwara et al, 2009;Vierna et al, 2009;Freire et al, 2010;Úbeda-Manzanaro et al, 2010a;Perina et al, 2011;Pinhal et al, 2011]. However, they also observed a homogenization process within each different type of 5S rDNA obtained, and hence they concluded that a mixed model between concerted and birth-and-death evolution is the most probable for the 5S rDNA multigene family.…”
Section: Evolution Of the 5s Rdna: Concerted Evolution Versus Birth-amentioning
confidence: 99%
“…However, many reports have been recently published in which the concerted evolution model did not explain the intragenomic divergence found in some organisms, mainly (but not exclusively) within the non-transcribed spacer (NTS) region (Rooney and Ward, 2005;Fujiwara et al, 2009;Vierna et al, 2009Vierna et al, , 2011Freire et al, 2010;Ú beda-Manzanaro et al, 2010;Perina et al, 2011;Vizoso et al, 2011). Other evolutionary models (birth-and-death evolution; mixed process of concerted and birth-and-death evolution (Nei and Rooney, 2005)) have been proposed to drive the evolution of 5S rDNA (Rooney and Ward, 2005;Fujiwara et al, 2009;Vierna et al, 2009Vierna et al, , 2011Freire et al, 2010;Ú beda-Manzanaro et al, 2010;Perina et al, 2011;Vizoso et al, 2011).…”
Section: Introductionmentioning
confidence: 99%